2017
DOI: 10.1155/2017/4951937
|View full text |Cite
|
Sign up to set email alerts
|

Chemicals Compositions, Antioxidant and Anti‐Inflammatory Activity of Cynara scolymus Leaves Extracts, and Analysis of Major Bioactive Polyphenols by HPLC

Abstract: Objective. Artichoke (Cynara scolymus L.) was one of the plant remedies for primary health care. The present study was focused on the determination of chemical composition, antioxidant activities, and anti-inflammatory activity and on analyzing its major bioactive polyphenols by HPLC. Methods. Artichoke Leaves Extracts (ALE) were analyzed for proximate analysis and phytochemical and antioxidant activity by several methods such as DDPH, ABTS, FRAP, and beta-carotene bleaching test. The carrageenan (Carr) model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 47 publications
6
37
2
Order By: Relevance
“…The in vitro assessment of antioxidant activity by various methods such as DDPH (2,2‐diphenyl‐1‐picrylhydrazyl), ABTS (2,20‐azinobis(3‐ethylbenzothiazoline‐6‐sulphonic acid) diammonium salt), FRAP (ferric reducing ability of plasma), and beta‐carotene bleaching test indicated that aqueous and ethanolic extract of artichoke possess high radical scavenging capacity (Ben Salem & Affes, ; da Silva Oliveira et al, ; Kollia, Markaki, Zoumpoulakis, & Proestos, ; Kollia, Markaki, Zoumpoulakis, & Proestos, ). Moreover, artichoke is categorized as an antioxidant rich vegetable, based on the comprehensive Antioxidant Food Database (Carlsen et al, ).…”
Section: Disscusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The in vitro assessment of antioxidant activity by various methods such as DDPH (2,2‐diphenyl‐1‐picrylhydrazyl), ABTS (2,20‐azinobis(3‐ethylbenzothiazoline‐6‐sulphonic acid) diammonium salt), FRAP (ferric reducing ability of plasma), and beta‐carotene bleaching test indicated that aqueous and ethanolic extract of artichoke possess high radical scavenging capacity (Ben Salem & Affes, ; da Silva Oliveira et al, ; Kollia, Markaki, Zoumpoulakis, & Proestos, ; Kollia, Markaki, Zoumpoulakis, & Proestos, ). Moreover, artichoke is categorized as an antioxidant rich vegetable, based on the comprehensive Antioxidant Food Database (Carlsen et al, ).…”
Section: Disscusionmentioning
confidence: 99%
“…It is hypothesized that the antioxidant activity of artichoke might be related to following compounds: (a) polyphenolics (caffeoylquinic acids and flavonoids) and (b) Sesquiterpenes (Ben Salem & Affes, ; Brown & Rice‐Evans, ; Gebhardt, ; Miccadei et al, ; Miláčková et al, ; Perez‐Garcia et al, ; Rahimuddin et al, ; Takei et al, ). 1.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, sprouting on paper tissues resulted in significant increase in protein as compared to sprouting on soil mixture in both seasons and rice straw in the second season (Table 2). According the results of Foti et al (1999) and Ben Salem et al (2017), artichoke sprouts contained higher content of protein as compared with that determined in seeds and leaves, respectively. Similar results were recorded by Abdallah et al (2009) who reported that that on dry weight basis, the protein content of sun flower sprouts was higher than that of the seeds.…”
Section: Crude Protein Contentmentioning
confidence: 84%
“…Artichoke ( Cynara scolymus L.) is a Mediterranean edible vegetable, which is known to be rich in natural antioxidants, among them hydroxycinnamic acids, vitamin C and flavones . The herbal formulation from this plant is commonly indicated as primary health care for different purposes . It was reported that artichoke exerted a considerable improvement in GPx activity in erythrocytes from a rat model .…”
Section: Major Medicinal Plants Used In Medication System As Anti‐agementioning
confidence: 99%